Identification and functional analysis of two P450 enzymes of Gossypium hirsutum involved in DMNT and TMTT biosynthesis. Issue 2 (16th August 2017) - Liu, Danfeng; Huang, Xinzheng; Jing, Weixia; An, Xingkui; Zhang, Qiang; Zhang, Hong; Zhou, Jingjiang; Zhang, Yongjun; Guo, Yuyuan
Summary: The homoterpenes ( 3E )‐4, 8‐dimethyl‐1, 3, 7‐nonatriene (DMNT) and ( E, E )‐4, 8, 12‐trimethyl‐1, 3, 7, 11‐tridecatetraene (TMTT) are major herbivore‐induced plant volatiles that can attract predatory or parasitic arthropods to protect injured plants from herbivore attack. In this study, DMNT and TMTT were confirmed to be emitted from cotton ( Gossypium hirsutum ) plants infested with chewing caterpillars or sucking bugs. Two CYP genes ( GhCYP82L1 and GhCYP82L2 ) involved in homoterpene biosynthesis in G. hirsutum were newly identified and characterized. Yeast recombinant expression and enzyme assays indicated that the two GhCYP82Ls are both responsible for the conversion of ( E )‐nerolidol to DMNT and ( E, E )‐geranyllinalool to TMTT. The two heterologously expressed proteins without cytochrome P450 reductase fail to convert the substrates to homoterpenes. Quantitative real‐time PCR (qPCR) analysis suggested that the two GhCYP82L genes were significantly up‐regulated in leaves and stems of G. hirsutum after herbivore attack. Subsequently, electroantennogram recordings showed that electroantennal responses of Microplitis mediator and Peristenus spretus to DMNT and TMTT were both dose dependent. Laboratory behavioural bioassays showed that females of both wasp species responded positively to DMNT and males and females of M. mediator could be attracted by TMTT. The results provide a better understanding of homoterpene biosynthesis in G. hirsutum and of the potential influence of homoterpenes on the behaviour of natural enemies, which lay a foundation to study genetically modified homoterpene biosynthesis and its possible application in agricultural pest control.